2020
DOI: 10.3350/cmh.2020.0018
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs of chronic hepatitis C in the era of direct-acting antiviral therapy

Abstract: The treatment of chronic hepatitis C (CHC) has been revolutionized in an era of all-oral direct-acting antivirals (DAAs) since 2014. Satisfactory treatment efficacy and tolerability can be provided by novel DAAs. Nevertheless, there are still some unmet needs and emerging issues in the treatment of CHC in the DAA era. Certain hard-to-cure populations are prone to have inferior treatment responses, including patients with severe liver decompensation, active hepatocellular carcinoma (HCC), and hepatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 68 publications
(129 reference statements)
2
46
0
2
Order By: Relevance
“…11 In the era of DAAs, where treatment efficacy and tolerability are no longer the major concerns, a comprehensive HCV care cascade is needed, including proper screening for unawareness of HCV, accurate diagnosis, and linking to medical care. 12 Although the amount of clinical interest is low, the findings of this study conducted by the Mongolian government for Hepatitis Prevention, Control and Elimination are meaningful. Moreover, this large sized study showed the effectiveness of LDV/SOF at a fixed dose and treatment duration in helping to promote universal healthcare for CHC in countries with resource-limited settings.…”
mentioning
confidence: 78%
“…11 In the era of DAAs, where treatment efficacy and tolerability are no longer the major concerns, a comprehensive HCV care cascade is needed, including proper screening for unawareness of HCV, accurate diagnosis, and linking to medical care. 12 Although the amount of clinical interest is low, the findings of this study conducted by the Mongolian government for Hepatitis Prevention, Control and Elimination are meaningful. Moreover, this large sized study showed the effectiveness of LDV/SOF at a fixed dose and treatment duration in helping to promote universal healthcare for CHC in countries with resource-limited settings.…”
mentioning
confidence: 78%
“…In contrast, in patients with incurable HCC and life expectancy of >1 year, the HCV treatment should be initiated immediately (Figure 1). 19,21 In the meantime, three populations, including patients with cirrhosis and HCV genotype 3, patients with previous DAA failures, and patients with decompensated cirrhosis require special considerations with different recommended DAA regimens, as summarized in Table 1, based on the 2020 Taiwan Consensus on Hepatitis C Management.…”
Section: Unmet Needs Of Chronic Hepatitis C (Chc) Management In the Dmentioning
confidence: 99%
“…Each of these steps is a critical hurdle that adds complexity, which prevents the healthcare system from eliminating HCV infection. [2,8,9] To accurately confirm ongoing HCV infection, laboratory testing typically begins with the detection of antibodies to HCV (anti-HCV), followed by the confirmation of the presence of HCV RNA in the blood of subjects who are anti-HCV seropositive.…”
Section: Introductionmentioning
confidence: 99%